If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -389 = 64 Reorder the terms: -389 + x = 64 Solving -389 + x = 64 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '389' to each side of the equation. -389 + 389 + x = 64 + 389 Combine like terms: -389 + 389 = 0 0 + x = 64 + 389 x = 64 + 389 Combine like terms: 64 + 389 = 453 x = 453 Simplifying x = 453
| x-5=x^2+2X+1 | | 8=3+x/9 | | x+9-(17)=24 | | b/5=b+2/6 | | 8z-4=3z-19 | | 2y^2-11y+5= | | 6=4x-12/4 | | X/18=4.5 | | X/15=20/30 | | -4x+7(-x-7)=-126 | | 3-8x+8=80 | | 64-9x-3= | | 3x^2+11x-14= | | 64-9x^9= | | 1/2+2x=50 | | x+(2x)=18 | | 64-9x^4= | | 8x^2-6x-2=125 | | 90=x+10 | | -1/9=t+1/3 | | 2(-10/9y+10)-8y=16 | | 7x^2+12x-4= | | 3x-15+17= | | (-10/9y+10)-8y=16 | | x-7/8=-1/8 | | 4/9+x=-5/9 | | 49+3x=7y | | -2r-1=-11 | | (-11/9+10)-8y=16 | | 6+5/y=y-2/y | | -10=-4+x/4 | | 18=7+N |